2013
DOI: 10.7567/apex.6.075501
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Evolution of Pulsed-Flux Ga-Polar GaN Nanorod Growth by Metal Organic Vapor Phase Epitaxy and Its Nucleation Dependence

Abstract: We fabricated selectively grown Ga-polar GaN nanorods by optimizing metal organic vapor phase epitaxy (MOVPE) growth parameters using continuous-and pulsed-mode approaches. Nucleation layers were grown using continuous mode with H 2 or N 2 as carrier gas, which resulted in pyramidal or hexagonal shapes, respectively. The growth mechanism of nanorods was further studied for the nucleation layer grown with the H 2 case, in which the pyramidal shape of the nucleation layer was observed to be flattened during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…However, the PL intensity decreased as the SiH 4 flow increased, indicating the reduced crystal quality of the GaN microrods [21]. To date, the majority of 3D GaN structures fabricated by selective area growth (SAG) have involved MOCVD with a continuous flux [21][22][23] or pulse-mode growth [12,[24][25][26], and MBE [27]. In contrast, there have been few reports on the growth of 3D GaN structures by SAG-HVPE because of the difficulty in achieving elongated structures [28].…”
Section: Introductionmentioning
confidence: 93%
“…However, the PL intensity decreased as the SiH 4 flow increased, indicating the reduced crystal quality of the GaN microrods [21]. To date, the majority of 3D GaN structures fabricated by selective area growth (SAG) have involved MOCVD with a continuous flux [21][22][23] or pulse-mode growth [12,[24][25][26], and MBE [27]. In contrast, there have been few reports on the growth of 3D GaN structures by SAG-HVPE because of the difficulty in achieving elongated structures [28].…”
Section: Introductionmentioning
confidence: 93%
“…Optimizing the pyramidal growth is less straightforward. Indeed, pulsed SAE tends to promote the growth of crystals with stable sidewalls, resulting in the observed truncated hexagonal pyramid like structures. By contrast, continuous flow commonly lead to pure pyramidal growth …”
Section: Growth Of the Microstructuresmentioning
confidence: 99%
“…In particular, selective area growth (SAG) by MOVPE is one of the important techniques for the improvement of GaN crystalline quality. It has been reported that GaN nanostructures are markedly sensitive to experimental conditions such as growth temperature, partial pressure, V/III ratio, and carrier gas . Therefore, various types of facets have been observed depending on these growth conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In this article, we focus on the formation of nanostructures such as nanowires to show the mechanism of morphology change and aspect ratio in GaN nanostructures under MOVPE condition. So, we compose several equilibrium crystal shapes on the basis of equilibrium Wulff construction using absolute surface energies The surface reconstructions of polar and semipolar (112¯2) and (11¯00) planes are taken into account on the basis of absolute surface energies and surface phase diagrams, which are interpreted by calculating Gibss free energy as a function of growth temperature and partial pressure.…”
Section: Introductionmentioning
confidence: 99%